Integrating Writing and Structural Engineering – An Exploration - Lloyd, Natalie; Ramiah, R. (2014)
Engineers do not need to know how to write. This statement expresses a common belief amongst engineering undergraduate students, which is often compounded by a resistance to communication practice. It is contrary to engineering industry and Engineers Australia Accreditation Board expectations, which value communication and rate written communication as a key competency required for engineers (Male, Bush and Chapman, 2009). Whilst communication skills appear to form an important part of engineering curricula, teaching these skills is often the responsibility of language specialists from a Humanities background. Collaboration between discipline lecturers and writing specialists has been the form of some interventions to enhance writing skills of undergraduate engineering students (Craig, Lerner and Poe 2008). However, communicating technological information involves interpreting and using specialised disciplinary discourse; content lecturers as disciplinary experts have a key role to play in teaching their students disciplinary discourse (Airey, 2011). This paper explores the realities of transforming engineering teaching practice within a core second year Civil Engineering unit of Structural Analysis to create space for teaching writing as disciplinary communicative practice through a strategic, enquiry approach to teaching and learning.